2020
DOI: 10.1002/gcc.22855
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a MALT lymphoma cell line carrying an API2‐MALT1 translocation

Abstract: MALT lymphomas with API2(BIRC3)‐MALT1 translocation usually have an indolent clinical course and rarely transform into aggressive lymphoma, and there have been no lymphoma cell lines carrying API2‐MALT1 translocation reported to date. We established a novel lymphoma cell line named BMA19, carrying the API2‐MALT1 translocation from a patient with histologic transformation of intestinal MALT lymphoma. The cells were suggested to carry API2‐MALT1 and MYC‐IGH translocations by chromosomal analysis, and these trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Recent studies illustrate that the change of MALT1 activity is associated with ERS, and NF-κB signal is also one of the triggers of ERS. 15 It was known that MALT1 plays a pivotal role in activating immune response by regulating and transducing NF-κB signaling. 13 We found that SCI/R injury activated NF-κB signaling and ERS, which suggested that NF-κB signaling might mediate the ERS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies illustrate that the change of MALT1 activity is associated with ERS, and NF-κB signal is also one of the triggers of ERS. 15 It was known that MALT1 plays a pivotal role in activating immune response by regulating and transducing NF-κB signaling. 13 We found that SCI/R injury activated NF-κB signaling and ERS, which suggested that NF-κB signaling might mediate the ERS.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies suggested that MALT1 is an essential intermediate in antigen receptor activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) in response to stimulation of a subset of G protein-coupled receptors. [13][14][15] Recent studies have shown that changes in MALT1 activity are related to ERS induction. ERS activates the NLRP3 inflammasome via NF-κB to promote IL-1β secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Its pathogenesis progresses in association with chronic inflammation (105). A gene fusion between apoptosisinhibitor-2 (API2) on chromosome 11 and the mucosa-associated lymphoid tissue translocation gene 1 (MALT1) on chromosome 18 formed the API2-MALT1 oncogenic chimera (106). This is the most common chromosomal translocation in MALT lymphomas and has disrupted the function of the MALT1 gene.…”
Section: Lima1 and Mucosa-associated Lymphoid Tissue Lymphomasmentioning
confidence: 99%